Perkembangan Kejeruan Bingai dalam Lintasan Sejarah (1770–1946) - Sadikin Manik (Medan Resource Center, 2024)
This study explores the historical dynamics of Kejeruan Bingai during the Langkat Sultanate era (1770–1946), addressing the limited scholarly attention to this local polity within North Sumatran historiography. The research focuses on the origins, political development, socio-religious life, factors of decline, and surviving material heritage of Kejeruan Bingai. Using a qualitative historical method, the study applies systematic stages of heuristics, source criticism, interpretation, and historiography. Data were obtained through field observations, in-depth interviews with local informants, and critical analysis of written sources. The findings demonstrate that Kejeruan Bingai emerged as part of the Langkat Sultanate’s political integration strategy, initiated by King Wan Jabar and institutionalized under Sultan Tengku Musa through the formation of Kejeruan administrative units. Bingai developed into a subordinate local kingdom led by five rulers and reached its peak during the reigns of Tengku Masrurah, Tengku Abdul Khani, and Tengku Muhammad Daud, marked by Islamic educational institutions, mosque construction, and colonial-era infrastructure development. This study’s novelty lies in its reconstruction of Kejeruan Bingai as an active local governance entity rather than a peripheral domain, offering a new interpretation of Langkat’s political structure and enriching local Islamic historiography in North Sumatra.